PENGARUH FEMALE CEO TERHADAP KUALITAS LAPORAN KEUANGAN: PREFERENSI RISIKO SEBAGAI PEMODERASI - NUR JAMALIYAH ISRAINI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2020)
The aim of this research is to examine the impact of female CEO on financial reporting quality. This reasearch also adds risk preferences to moderate the relations of female CEO and financial reporting quality. Female CEO is measured by CEO gender dummy. Absolute discretionary accrual is the proxy of financial reporting quality. Audit opinions are also added as alternative measurement of financial reporting quality. This reasearch used 1653 non financial-companies listed in Indonesia Stock Exchange period 2014-2018, selected based on several criteria. Based on the result, female CEO has a negative effect on absolute discretionary accruals which indicate that it can improve the financial reporting quality. However, the effect didn’t show the significant effect. Female CEO have positive significant on unqualified audit opinion that indicate higher quality of financial reporting. Risk preference can moderate the relationship of female CEO and financial reporting quality. Female CEO who have risk taking preference tend to do earnings management which can reduce the quality of financial reporting.